A spotting scope model with a convertible lens - Shakirov, A.L. (Recent Contributions to Physics, 2014)
The aim of the study is to develop a spotting scope model with a convertible lens consisting of two relatively shortfocus lenses. A theoretical model of a spotting scope with a convertible lens allowing estimation of magnification was developed. The designed model was compared with the existing classical spotting scope scheme. A stand intended for the test of pairs of lenses allowing determination of geometric parameters of the convertible lens and the limits of focal distance changing was constructed. A number of working dummies of the spotting scope with convertible lenses was constructed using the obtained experimental data and theoretical developments. A spotting scope model with a convertible lens may find a wide application both in scientific research tools and in household goods.